2022
DOI: 10.1155/2022/4495757
|View full text |Cite
|
Sign up to set email alerts
|

Medical Conditions, Oral Health Practices, and Barriers to Treatment among Patients Visiting a Teaching Dental Hospital in Eastern Saudi Arabia

Abstract: Objective. To assess the prevalence of medical conditions, oral hygiene practices, and dental visits among patients who attended a teaching dental hospital in Dammam, Saudi Arabia. Materials & Methods. This retrospective cross-sectional study used patient records from 2009 to 2015 from the dental hospital of the College of Dentistry Imam Abdulrahman Bin Faisal University, Dammam. Patients’ demographics, medical history, oral hygiene practices, reasons for attending the facility, attendance patterns, and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
5
6
1
1
Order By: Relevance
“…This study assessed the prevalence and various types of medical comorbidities amid patients in oral surgery clinics by examining the records of patients who were treated during a single academic period of 1 year at the College of Dentistry, Jazan University. The main findings of the study revealed that out of the total patients observed (n=640), the prevalence of patients with medical comorbidity was 27.5% (n=176), which is similar to that observed in recent studies by Lakhani et al (23.4%; n=1867) [ 41 ], Alonaizan et al (25.7%; n=1502) [ 42 ], Chandler et al (30.6%;n=716) [ 43 ], Shetty et al (33%; n=725) [ 38 ], Gaphor et al (35.24%; n=1200) [ 44 ], and Sanguansin et al (30.5%; n=712) [ 45 ]. Among these studies, however, the study by Lakhani et al was done in oral surgery patients for a similar time period (1 year), while the findings of Alonaizan et al [ 42 ] were observed in a Saudi academic dental hospital over a period of 6 years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study assessed the prevalence and various types of medical comorbidities amid patients in oral surgery clinics by examining the records of patients who were treated during a single academic period of 1 year at the College of Dentistry, Jazan University. The main findings of the study revealed that out of the total patients observed (n=640), the prevalence of patients with medical comorbidity was 27.5% (n=176), which is similar to that observed in recent studies by Lakhani et al (23.4%; n=1867) [ 41 ], Alonaizan et al (25.7%; n=1502) [ 42 ], Chandler et al (30.6%;n=716) [ 43 ], Shetty et al (33%; n=725) [ 38 ], Gaphor et al (35.24%; n=1200) [ 44 ], and Sanguansin et al (30.5%; n=712) [ 45 ]. Among these studies, however, the study by Lakhani et al was done in oral surgery patients for a similar time period (1 year), while the findings of Alonaizan et al [ 42 ] were observed in a Saudi academic dental hospital over a period of 6 years.…”
Section: Discussionsupporting
confidence: 88%
“…The main findings of the study revealed that out of the total patients observed (n=640), the prevalence of patients with medical comorbidity was 27.5% (n=176), which is similar to that observed in recent studies by Lakhani et al (23.4%; n=1867) [ 41 ], Alonaizan et al (25.7%; n=1502) [ 42 ], Chandler et al (30.6%;n=716) [ 43 ], Shetty et al (33%; n=725) [ 38 ], Gaphor et al (35.24%; n=1200) [ 44 ], and Sanguansin et al (30.5%; n=712) [ 45 ]. Among these studies, however, the study by Lakhani et al was done in oral surgery patients for a similar time period (1 year), while the findings of Alonaizan et al [ 42 ] were observed in a Saudi academic dental hospital over a period of 6 years. In terms of comparison with studies with a large sample size, our results showed a similar prevalence as that observed by Smeets et al (28.2%; n=29 424) [ 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…Oleh karena itu, dokter gigi perlu memahami potensi komplikasi yang dapat terjadi sebagai konsekuensi dari perawatan gigi pada pasien dengan kelainan sistemik baik ketika pra-perawatan atau pengobatan pasca perawatan atau diindikasikan perawatan darurat. Pasien dengan kompromi medis hanya boleh dirawat di lingkungan rumah sakit di mana jika muncul masalah darurat, dapat segera ditangani secara terkendali (Alonaizan et al, 2022;Bakardjiev, 2019;Bakardjiev, 2011;Ganda, 2006) Maksud kegiatan pengabdian masyarakat ini adalah untuk memberikan kemampuan penguasaan pengetahuan mengenai penatalaksanaan pasien dengan syok anafilaksis dan penyakit sistemik pada praktik dokter gigi, sehingga dapat terhindar dari komplikasi maupun kematian. Adapun tujuan dari dilakukannya pengabdian masyarakat adalah untuk upaya peningkatan pengetahuan dan keterampilan kesehatan untuk dokter gigi yang diselenggarakan dalam bentuk kegiatan dengan pendekatan promotif dan preventif yang dilaksanakan secara terpadu, menyeluruh dan berkesinambungan.…”
Section: Pendahuluanunclassified
“…Each identified condition may affect dental care in a unique way, such as a drug prescribed post-intervention in certain patients with medical compromise may cause problems during the administration of local anesthetics or may interact with pain medications prescribed afterward. [5][6][7][8] Dental and oral care in patients with systemic diseases is a critical aspect of the dental practice, so if neglected, it can lead to adverse consequences. 14,15 Therefore, dentists need to understand the potential complications that can result from dental treatment in patients with systemic disorders when either pre-treatment or posttreatment, or emergency treatment is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with medical compromise should only be treated in a hospital setting where, if an emergency occurs, it can be treated promptly and controlled. [5][6][7][8] Patients with systemic disease may experience oral signs, including ulceration, this case, the report discusses the incidence of systemic diseases in dental practice and the readiness of dentists in its management. Most systemic disorders ever found in dentistry practices were hypertension (96.2%), while other cases were diabetes (89.2%), heart disorders (65.1%), asthma (47%), allergies (45.8%), stroke (37.3%), blood disorders (27.7%), kidney disorders (25.3%), thyroid disorders (24.1%), liver disorders (14.5%), and others (2.4%).…”
Section: Introductionmentioning
confidence: 99%